Sistem Informasi Manajemen Aset Bendung Serdang BWS Sumatera II Menggunakan Metode Straight Line dan Simple Additive Weighting - Afandi, Muhammad Fikri; Nasution, Muhammad Irwan Padli (Jurnal Teknologi dan Manajemen Informatika, 2023)
Serdang Dam is one of the water resource dams managed by the Regional Office of the Sumatra II River Basin, which is a technical implementing unit of the Ministry of Public Works and Public Housing located in North Sumatra Province. Asset management at Serdang Dam has been done manually through recording and bookkeeping, which are then inputted into a document file. This system has several shortcomings, including difficulties in tracing asset information in each activity and the lack of a basis for asset depreciation and acquisition calculations, resulting in suboptimal asset management processes. To overcome these issues, research will be conducted to facilitate the management of Serdang Dam assets by developing an asset management information system using the Straight Line and Simple Additive Weighting methods. The findings of this research will provide a solution to the existing problems by creating a system that can assist in managing Serdang Dam assets in all its activities.